Helping young children understand inherited cancer predisposition syndromes using bibliotherapy. Issue 4 (31st March 2021) - Schlub, Georgina M.; Crook, Ashley; Barlow‐Stewart, Kristine; Fleming, Jane; Kirk, Judy; Tucker, Kathy; Greening, Sian
Abstract: Communication with children about hereditary conditions in the family can be difficult for parents. Yet, good communication strategies are leading determinants of adaptation and resilience. With inherited cancer predisposition syndromes that can affect young children such as Li‐Fraumeni syndrome (LFS) and hereditary pheochromocytoma and paraganglioma syndrome (HPPS), genetic testing and subsequent surveillance in at‐risk children is the optimal intervention. Given testing often commences early, providing children and their parents with appropriate genetic counseling and communication strategies is important for informed decision making. To inform such communication strategies, we used a bibliotherapeutic framework, where stories are delivered prescriptively (i.e., 'bibliotherapy'), to develop a psycho‐educational resource for children aged 5–10 years old at risk of either LFS or HPPS. Illustrated storybooks for children were created based on models of developmental comprehension. To ascertain their experience, parents were invited to read a storybook to their child/ren and participate in semi‐structured qualitative interviews. Transcripts were analyzed thematically using a general inductive approach. The bibliotherapeutic resource reportedly supported parents with communication about these issues without raising emotional distress in either themselves or their children. The key stages of a bibliotherapeutic interaction were facilitated by the use of this resource, and all parents reported that it would have been useful when their children were first tested and/or diagnosed. This study lays the foundation for the application of bibliotherapy as a psycho‐educational intervention in genetic counseling and demonstrates that bibliotherapy may improve the process of communication between parents and children regarding pediatric‐inherited cancer syndromes.